Cluster evolution during the early stages of heating explosives and its relationship to sensitivity: a comparative study of TATB, β-HMX and PETN by molecular reactive force field simulations1. Issue 18 (14th May 2015) - Wen, Yushi; Zhang, Chaoyang; Xue, Xianggui; Long, Xinping
<x xml:space="preserve">Abstract</x> The clustering mechanism of heating TATB, HMX and PETN was strongly influenced by their oxygen balance and was related to their sensitivity.